The Big book of reel murders : stories that inspired great crime films - Penzler, Otto. (New York : Vintage Crime/Black Lizard, 2019)
Edgar Award-winning editor Penzler's new anthology rolls out the red carpet for the stories that Hollywood hits are made of. He delivers the director's cut of classic short stories that inspired some of Tinsletown's most memorable films. ... Including... works by:Authors include: Edgar Allan Poe, Cornell Woolrich, Aldous Huxley, Ian Fleming, Robert Louis Stevenson, Budd Schulberg, O. Henry, W. Somerset Maugham, and many more.--
The suspense is killing me -- Stop, you're killing me -- Isn't this thrilling? -- Oh, the horror! -- Isn't it a crime? -- I love you to death - Is there a detective in the house?
Keywords: Detective and mystery stories; Noir fiction